A new species of the catfish genus Trichomycterus from the La Plata River basin, southern Brazil, with comments on its putative phylogenetic position (Siluriformes: Trichomycteridae) - Datovo, Aléssio; Carvalho, Murilo; Ferrer, Juliano (Zootaxa, 2012)
The genus Trichomycterus is a highly diverse group of Neotropical catfishes that encompass almost 60% of all the cur-rently recognized species of the Trichomycteridae. A new species of this genus, T. perkos, is herein described from tribu-taries of the Paranapanema and Uruguai River basins, southern Brazil. The new species exhibits a remarkable ontogeneticchange in its pigmentation, having a unique color pattern when adult. The adult pigmentation consists of three wide darkbrown stripes, located in an inner skin layer of trunk and caudal peduncle, combined with a superficial light brown freck-led pattern on the dorsum and caudal peduncle. Small, presumably juvenile specimens lack the superficial freckles butalready have the dark stripes, thus resembling the color pattern of a few other congeners. Nevertheless, several unequiv-ocal morphological features distinguish both juveniles and adults of T. perkos from these congeners. In spite of the diffi-culties in estimating phylogenetic relationships within Trichomycterus, the new species is tentatively proposed as being the sister-taxon of a small group of species composed by T. crassicaudatus, T. igobi, and T. stawiarski.